Cost-effectiveness and budget impact of Empirical vitamin D therapy on unintentional falls in older adults in the UK - J Smith; J S Davies; C D Poole (BMJ Open)
Objectives To evaluate the health outcomes and economics associated with the current guidance relating to the prevention of falls in the elderly through vitamin D supplementation.Setting UK.Participants UK population aged 60 years and above.Interventions A Markov health state transition model simulated patient transitions between key fall-related outcomes using a 5-year horizon and annual cycles to assess the costs and benefits of empirical treatment with colecalciferol 800 iu daily.Primary and secondary outcome measures Costs and health outcomes attributable to fall prevention following vitamin D supplementation.Results Our model shows that treating the UK population aged 60 years and above with 800 iu colecalciferol would, over a 5-year period: (1) prevent in excess of 430 000 minor falls; (2) avoid 190 000 major falls; (3) prevent 1579 acute deaths; (4) avoid 84 000 person-years of long-term care and (5) prevent 8300 deaths associated with increased mortality in long-term care. The greatest gains are seen among those 75 years and older. Based on reduction in falls alone, the intervention in all adults aged 65+ is cost-saving and leads to increased quality adjusted life years. Treating all adults aged 60+ incurs an intervention cost of £2.70bn over 5 years, yet produces a −£3.12bn reduction in fall-related costs; a net saving of £420M. Increasing the lower bound age limit by 5-year increments increases budget impact to −£1.17bn, −£1.75bn, and −£2.06bn for adults 65+, 70+ and 75+, respectively.Conclusions This study shows that treatment of the elderly UK population with colecalciferol 800 iu daily would be associated with reductions in mortality and substantial cost-savings through fall prevention.